Persistence of multiple patterns and intraspecific polymorphism in multi-species Müllerian communities of net-winged beetles - Bocek, Matej (Front Zool, 2019)
BACKGROUND: In contrast to traditional models of purifying selection and a single aposematic signal in Müllerian complexes, some communities of unprofitable prey contain members with multiple aposematic patterns. Processes responsible for diversity in aposematic signaling are poorly understood and large multi-species communities are seldom considered. RESULTS: We analyzed the phylogeny and aposematic patterns of closely related Eniclases net-winged beetles in New Guinea using mtDNA and nextRAD data. We suggest three clades of closely related and incompletely reproductively isolated lineages, detail the extent of polymorphism among Eniclases, and categorize their low-contrast aposematic patterns. The warning signal of Eniclases consists of body shape and color, with ambiguous color perception under some circumstances, i.e., when resting on the undersides of leaves. Field observations suggest that perception of the aposematic signal is affected by beetle behavior and environmental conditions. Local communities containing Eniclases consisted of 7–85 metriorrhynchine species assigned to 3–10 colour patterns. CONCLUSION: As a result, we suggest that under certain light conditions the aposematic colour signal is less apparent than the body shape in net-winged beetle communities. We document variable environmental factors in our study area and highly diverse multi-species communities of other net-winged beetles. Which implies dynamically changing community structure in space and time. Variable environmental conditions and diverse community composition are suggested to be favorable for the persistence of multiple aposematic patterns, imperfect mimics, and intraspecific polymorphism. Further research should identify the relative effect of these factors on purifying selection and the alleles which are responsible for phenotypic differences. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12983-019-0335-8) contains supplementary material, which is available to authorized users.